Current trends in jurisprudence regarding the protection of fundamental human rights in relation to the grounds for optional refusal of extradition of a person to the Russian Federation - Pătrăuș, Mihaela Elvira (International Journal of Legal and Social Order, 2023)
The phrase "security and public safety" has multiple meanings and can be analyzed by referring to the protection of fundamental human rights during judicial proceedings, including in the field of international judicial cooperation in criminal matters. A request for the passive extradition of a national of a member state or a third country, requires the executing state to check (if the extradition affects the rights included in the content of art. 19 paragraph (2) of the Charter of Fundamental Rights of the European Union (CFREU). This paper aims to analyze the optional reason for refusing the extradition of a person to the Russian Federation, in the current international context, through the lens of national and European jurisprudence in the matter.